Effect of Pulse Duration on Quality Characteristics of Blind Hole Drilled in Glass by ECDM. Issue 13 (2nd October 2016) - Gupta, Pankaj Kumar; Dvivedi, Akshay; Kumar, Pradeep
Abstract : Electrochemical discharge machining (ECDM) has proven its usefulness for micro-machining of hard, brittle, and nonconductive materials. Pulse duration is one of the most important process parameters in ECDM. The present article investigates the effect of pulse duration on aspect ratio of glass material machined by ECDM. An effective range of pulse duration was identified experimentally to achieve better control on the quality characteristics. The quality characteristics measured were machining depth, surface damage, aspect ratio, and tool wear. Results reveal that a limited range of pulse duration affects the quality characteristics leading to high aspect ratio. Further, values of process parameters for high aspect ratio of holes were identified. Effect of applied voltage on tool wear was also investigated.